THE EFFECT OF WORK MOTIVATION, ORGANIZATIONAL CULTURE, AND WORK-LIFE BALANCE ON GENERATION Z JOB SATISFACTION IN SUKABUMI CITY AND THE ROLE OF JOB SATISFACTION ON TURNOVER INTENTION - Sulistia Nanda Apriani (Journal of Social and Economics Research, 2026)
This investigation explores the manner in which work motivation, organizational culture, and work-life balance contribute to shaping job satisfaction levels. This investigation explores the manner in which work motivation, organizational culture, and work-life balance contribute to shaping job satisfaction levels among members of Generation Z employed in Sukabumi City, while simultaneously examining whether job satisfaction functions as a mediating link between these three factors and the tendency toward turnover intention. To achieve this, the study applies a quantitative methodology framed within an associative-causal design, with information collected from a total of 100 participants through an internet-based survey using a purposive sampling approach. Eligibility for participation was restricted to individuals from Generation Z aged between 20 and 27 who had accumulated a minimum of six months in professional employment. The resulting data were subsequently examined using Partial Least Square-Structural Equation Modeling (PLS-SEM), executed with the assistance of SmartPLS software, version 4.0. The findings reveal that both organizational culture and work-life balance exert a positive and significant influence on job satisfaction, whereas work motivation has a notably negative effect on it. Furthermore, job satisfaction was found to negatively and significantly impact turnover intention, functioning as a meaningful mediating variable linking all three predictors to employees' intention to leave their jobs. These results add to existing human resource management knowledge by highlighting job satisfaction as a key psychological pathway shaping how Generation Z employees behave in the workplace. From a practical standpoint, companies operating in Sukabumi City are encouraged to give greater attention to work-life balance initiatives, cultivate a constructive organizational culture, and align motivational strategies with employees' psychological well-being in order to retain Generation Z talent more effectively.